Islamic Economics and the Economy of Indian Muslims: New Delhi, India. Dhu al Hiijah 17-20, 1409/ July 21-24, 1989 (American Journal of Islam and Society, 1989)
The International Seminar on Islamic Economics and the Economy ofIndian Muslims was held July 21-24, 1989 in the Convention Center of HamdardUniversity, New Delhi, India, under the auspices of the Institute ofObjective Studies (IOS). The Seminar was the first of its kind in India. Therewere 10 sessions, with over 60 participants, on various aspects of IslamicEconomics as well as on the economy of Indian Muslims. In addition therewere inaugural and plenary sessions, and a public lecture. All the sessionswere well-attended. Conference delegates and participants came from all overIndia, as well as Egypt and the U.S. A number of scholars from other countriescould not attend the Conference because of the denial of visa for attendingthe Conference by the Indian Embassies in their respective countries.The Conference convened on Friday, July 21, 1989 at 1190 A.M. withthe inaugural session chaired by Dr. S. Z. Qasim, Vice-Chancellor of JamiaMillia Islamia, New Delhi. After the welcome speech by Mr. A. R. Agwan,Director of the IOS, Dr. Manzoor Alam, Chairman of the IOS, introducedthe 10s and its activities. The inaugural address was delivered by Dr. A.R. Kidwai, Chancellor, Aligarh Muslim University (AMU). Following that,the keynote address was given by Dr. F. R. Faridi of AMU, who was alsothe convenor of this seminar.Among the foreign delegates were Dr. Shawki Ismail Shehata of FaisalIslamic Bank of Egypt, Prof. Syed Iqbal Mahdi (who is the Secretary ofthe AMSS Economics Discipline Group),and Dr. A. Q. J. Shaikh from theU.S.A., and Dr. M. Ayub Munir from Pakistan.The Conference organizers had carefully selected the topics which weretimely and relevant both in terms of Islamic economics and the economyof Indian Muslims. Each session had 4 to 5 papers. The following were someof the topics:1. Employment Situation of Indian Muslims: An Appraisal ofits Nature and Magnitude2. Islamic Banking: Theory and Practice3. An Islamic Approach to Economic Development ...